2019
DOI: 10.1159/000496218
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Prevalence of Vascular Calcification in Different Types of Arteries and Influencing Factors in Maintenance Peritoneal Dialysis Patients

Abstract: Objective: To investigate the occurrence of vascular calcification (VC) in different types of arteries in patients with maintenance peritoneal dialysis (PD) patients and its influencing factors. Methods: This study enrolled PD patients with stable status who has received PD treatment for more than 6 months in Peking University People’s Hospital. We used plain X-ray films of abdomen, pelvis, and hands to quantitatively evaluate VC of large artery (abdominal aorta, iliac artery), medium artery (femoral artery, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
3
26
1
1
Order By: Relevance
“…Many underlying risk factors could promote transform of vascular smooth muscle cells to chondrocyte‐like or osteoblast‐like cells. These factors include P, Ca, iPTH, inflammatory cytokines, oxidative stress and advanced glycation end products . In Yang's study, they found that bovine aortic smooth muscle cells cultures can undergo a phenotypic transition into mature osteoblasts when cultured in the presence of beta‐glycerophosphate.…”
Section: Discussionmentioning
confidence: 99%
“…Many underlying risk factors could promote transform of vascular smooth muscle cells to chondrocyte‐like or osteoblast‐like cells. These factors include P, Ca, iPTH, inflammatory cytokines, oxidative stress and advanced glycation end products . In Yang's study, they found that bovine aortic smooth muscle cells cultures can undergo a phenotypic transition into mature osteoblasts when cultured in the presence of beta‐glycerophosphate.…”
Section: Discussionmentioning
confidence: 99%
“…[6], ðàñïðîñòðàí¸ííîñòü êàëüöèôèêàöèè êîðîíàðíûõ àðòåðèé ïàöèåíòîâ ñ ÕÁÏ â äîäèàëèçíûé ïåðèîä ñîñòàâèëà 40 % ïî ñðàâíåíèþ ñ 5-13 % â îáùåé ïîïóëÿöèè, [8]. Äëèòåëüíîñòü äèàëèçíîãî ëå÷åíèÿ ïî íàøèì ñâåäåíèÿì îêàçàëàñü çíà÷èìûì ôàêòîðîì, ñâÿçàííûì ñ âûðàaeåííîñòüþ ÊÁÀ (ð0,001) è îáóñëîâëåíî, î÷åâèäíî, äëèòåëüíîé ýêñïîçèöèåé ôàêòîðîâ ðèñêà ñåðäå÷íî-ñîñóäèñòîé ïàòîëîãèè ó äàííîé êàòåãîðèè ïàöèåíòîâ, ÷òî ïîäòâåðaeäàþò äàííûå ðÿäà èññëåäîâàíèé [9][10]. Ïðîâåä¸ííûé ìåaeãðóïïîâîé àíàëèç â îáñëåäîâàííîé ãðóïïå ïîêàçàë, ÷òî ïðè íàðàñòàíèè âûðàaeåííîñòè ÊÁÀ ó ïàöèåíòîâ áûëè áîëåå âûðàaeåíû íàðóøåíèÿ ôîñôîðíî-êàëüöèåâîãî îáìåíà (âûñîêèé óðîâåíü Ð è ïðîèçâåäåíèå Ñà  Ð), ÿâëåíèÿ ãèïåðïàðàòèðåîçà.…”
Section: ìàòåðèàë è ìåòîäûunclassified
“…Meanwhile, inadequate dialyzer membrane biocompatibility aggravates inflammation and oxidative stress when the artificial materials contact with blood [11]. Oxidative stress and inflammation are also important factors that contribute to vascular calcification [12,13]. Inversely, PD has little influence on hemodynamics and better preservation of residual renal function, so PD patients may possibly be at a lower cardiovascular risk [14].…”
Section: Introductionmentioning
confidence: 99%